Bhoga kārikā of Sadyojyoti with the commentary of Aghora Śiva - Aghoraśivācārya; Sadyojyotiḥ; Borody, W. A.; Sadyojyoti ca. 9. Jh.; Aghoraśivācārya; Aghoraśivācārya (Delhi [u.a.] Motilal Banarsidass, 2005)
Text on the doctrines of Kashmir Śaivism
Text of Bogakārikā and commentary in Sanskrit (roman); translation and introductory matter in English
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Kashmir Śaivism -- Doctrines; Kommentar; Quelle